(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe self-care practices and associated factors among elderly outpatients with hypertension at Hanoi Medical University Hospital. Methods: A cross-sectional study included 323 elderly outpatients with hypertension who met the selection criteria. Results: This study revealed that 65.94% had good level of self-care practices. Gender (OR = 2.23, 95% CI: 1.34 – 3.75), place of residence (OR = 0.73, 95% CI: 0.56 – 0.98), duration of hypertension (OR = 1.61, 95% CI: 1.26 – 3.35), level of self-care knowledge (OR = 1.45, 95% CI: 1.26 – 2.44), and participation in hypertension support groups/clubs (OR = 1.93, 95% CI: 1.32 – 3.05) were statistically associated with a good level of self-care practices. Conclusions: The rate of elderly people with hypertension practicing good self-care is moderate. Improving self-care knowledge and encouraging group or club participation are key to enhancing and sustaining these practices.